2017
DOI: 10.1108/ijrdm-04-2016-0050
|View full text |Cite
|
Sign up to set email alerts
|

Small family grocers’ inherent advantages over chain stores: a review

Abstract: Purpose As a result of the growth of the modernization of retailing, small family grocers have suffered because of the disadvantages of their limited operating resources in comparison to those of corporate chain retailers. The purpose of this paper is to use the biological analogy of natural selection to illustrate how the idea of retail coexistence rather than mutually exclusive competition can work to the benefit of small family grocers. The inherent differences between chain retailers and small family groce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 58 publications
(86 reference statements)
0
15
0
1
Order By: Relevance
“…This is generally expected since past studies have found communion-oriented people with whom friendship can be easily developed to be more likable (Wortman and Wood, 2011). Particularly, the small independent grocer context may privilege consumers’ direct perception of the storeowner without the interference of an organisational image (Srichookiat and Jindabot, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is generally expected since past studies have found communion-oriented people with whom friendship can be easily developed to be more likable (Wortman and Wood, 2011). Particularly, the small independent grocer context may privilege consumers’ direct perception of the storeowner without the interference of an organisational image (Srichookiat and Jindabot, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the service triangle, the customers are likely to expect the employees' performance based on the promises communicated by the organisation's marketing activities such as advertising and other promotional activities (Bitner, 1995). This expectation is different in the context of small independent retailers because customer attitude towards the storeowner is not influenced by the organisational promises (Srichookiat and Jindabot, 2017). In contrast, customers have a greater opportunity to interact with the same storeowner and that naturally accommodates the establishment of a service relationship.…”
Section: Development Of Framework and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…This facilitates direct contact between the owner and customer, which promotes relationship building. Small retailers can react quickly to changing customer needs (Srichookiat & Jindabot, 2017;Kelso, 2018). The strategic management decisions of small businesses are to a large degree dictated by the market.…”
Section: Literature Review and Conceptual Framework 21 South African Retail Market Structurementioning
confidence: 99%